DISCOURSE PHENOMENA IN MEANING MAKING FOR GLOBAL COMMUNICATION - Salam, Md. Abdus (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Global communication currently plays a crucial and highly significant role in both first language (L1) and foreign language (L2) learning situations. This occurs for various reasons, including international commerce, politics, higher education, immigration, and tourism. This article critically examines discourse phenomena in global communication, highlighting discourse metonymy, shifters, and textual metaphor as the discourse techniques used in metadiscourse to enhance communication and meaning creation in global contexts.Based on secondary and tertiary data, this study employs qualitative data analysis. Lev Vygotsky's 1962 interactional theory is used to comprehend communication theory. The purpose of this study is to answer the research question: How beneficial and acceptable are discourse phenomena in terms of meaning-making and global communication? The researcher finds that each of these discourse phenomena plays an important role in the meaning-making process, making communication clearer and more effective for L2 learners, whether at the vocabulary, clause, or sentence level in written texts or oral expression. As a result, the researcher recommends these discourse phenomena to students, teachers, linguists, and researchers for effective and appropriate global communication.